2022
DOI: 10.3390/ijms232314889
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene Polyamine Triazoles: Synthesis, Aggregation and DNA Binding

Abstract: Artificial gene delivery systems are in great demand from both scientific and practical biomedical points of view. In this paper, we present the synthesis of a new click chemistry calix[4]arene precursor with free lower rim and new water-soluble calixarene triazoles with 12 amino-groups on the upper rim (one with free phenol hydroxyl groups and two another containing four butyl or tetradecyl fragments). Aggregation in the series of amino-triazole calixarenes of different lipophilicity (calixarene with free phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The addition of calixarenes 3 , 4 and 8 to DNA at a calixarene concentration of 5 μM led to the compactization of DNA from 562 nm to 150–100 nm and low values of the polydispersity index ( Figure S6 ). Previously [ 24 ], it was shown that the addition of calixarenes 3 and 4 to DNA does not cause changes in the native DNA structure, according to the circular dichroism (CD) method. The addition of calixarene 7 to DNA did not significantly decrease the average hydrodynamic diameter of the calixarene–DNA double system, even at an equimolar ratio of 1:1 (50 μM) ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of calixarenes 3 , 4 and 8 to DNA at a calixarene concentration of 5 μM led to the compactization of DNA from 562 nm to 150–100 nm and low values of the polydispersity index ( Figure S6 ). Previously [ 24 ], it was shown that the addition of calixarenes 3 and 4 to DNA does not cause changes in the native DNA structure, according to the circular dichroism (CD) method. The addition of calixarene 7 to DNA did not significantly decrease the average hydrodynamic diameter of the calixarene–DNA double system, even at an equimolar ratio of 1:1 (50 μM) ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…Solvents were purified according to standard methods. 3-Bis[2-(tertbutoxycarbonylamino)ethyl]propargylamine, 25,26,27,28-tetrahydroxycalix[4]arene, 5,11,17,23-tetraazo-25,26,27,28-tetrahydroxycalix[4]arene, 5,11,17,23-tetraamino-25,26,27,28-tetrahydroxycalix[4]arene [ 33 , 34 , 35 ] and 5,11,17,23-tetraazido-25,26,27,28-tetrahydroxycalix[4]arene, 5,11,17,23-tetraazido-25,26,27,28-tetratetradecyloxycalix[4]arene [ 23 , 24 ] were prepared following procedures in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations